Multivariable control of a rougher flotation cell - Van Schalkwyk, Theo (Department of Chemical Engineering, 2015)
This project focussed on the investigation, development and evaluation of a closed loop control system on a rougher flotation cell that could improve PGM flotation performance. A PGM rougher flotation cell equipped with Online Stream Analysis (OSA) and machine vision system (SmartFroth) was used during the investigation. Online measurements included bubble velocity, average bubble area, bubble colour; Pt, Ni and Cu concentrate grade and concentrate flow rate and density. Air addition and pulp level was used as the manipulated variables.